Consumers' willingness to pay for low pesticide fresh vegetable Products in the Jaffna municipality area - Anushiya, T.; Sooriyakumar, K. (University of Jaffna, 2006)
In many of the developing countries, health risks associated with pesticide residue have been a matter of concern for many years. The excess and careless use of agrochemicals in Sri Lanka have directly led to cancer and also to on the increase in number of deaths by pesticide poisoning. There is also danger posed to the environment by indiscriminate use of pesticides. Health risk associated with pesticide residue is being discussed in several forums. Jaffna district is one of the high potential areas for agriculture production but presently pesticides are intensively used in agriculture in this district. This study examines the relationship between willingness to pay (WTP) for low pesticide residue fresh vegetable products by consumers in Jaffna municipality area and the various socioeconomic variables that affect WTP. One hundred and fifty households were selected randomly from the Jaffna municipality area to collect data. A pre tested questionnaire was used to interview the selected households and collect data during the period from July to November, 2004. A Tobit model was developed to analyze willingness to pay for low pesticide residue fresh products. Tobit analysis is the more theoretically appropriate method for WTP data sets. In this model, respondent's education (EDU), income (INCOME), vegetarianism (VEG), number of times respondent's eat outside the home (EAT OUT), number of family members who have studied up to A/L and number of graduates in the family are used as explanatory variables. The dependent variable is the WTP for low pesticide residue fresh products. The analytical results shows that the respondent's education, family income, number of family members studied up to A/L, number of graduates in the family and number of times people eat outside the home positively influences WTP for low pesticide products and also when family members are vegetarian it positively influence the WTP. But in this result the only estimate for respondent's education is significant at 5% level. .